2013
DOI: 10.1155/2013/709493
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Fish Oil on Serum of TNFα, IL-1β, and IL-6 Oxidative Stress Markers in Multiple Sclerosis Treated with Interferon Beta-1b

Abstract: Multiple sclerosis (MS) is a chronic inflammatory disease, which leads to focal plaques of demyelination and tissue injury in the central nervous system. Oxidative stress is also thought to promote tissue damage in multiple sclerosis. Current research findings suggest that omega-3 polyunsaturated fatty acids (PUFAs) such as eicosapenta-enoic acid (EPA) and docosahexaenoic acid (DHA) contained in fish oil may have anti-inflammatory, antioxidant, and neuroprotective effects. The aim of the present work was to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(80 citation statements)
references
References 43 publications
6
71
0
3
Order By: Relevance
“…They are proven to have neuroprotective effects as well as antiinflammatory, antithrombotic and immunomodulatory functions [6] , besides a beneficial role in brain growth and function. Subsequently, omega-3 polyunsaturated fatty acids have been linked to improved childhood development when ingested during pregnancy [7] .…”
Section: Introductionmentioning
confidence: 99%
“…They are proven to have neuroprotective effects as well as antiinflammatory, antithrombotic and immunomodulatory functions [6] , besides a beneficial role in brain growth and function. Subsequently, omega-3 polyunsaturated fatty acids have been linked to improved childhood development when ingested during pregnancy [7] .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, as recent published studies have accurately demonstrated, supplementation with omega-3 FAs improves systolic LV function and endothelial function as well as decreases markers of inflammation in CHF of non-ischemic origin (37) and other clinical conditions (38, 39). Therefore, it is entirely reasonable to postulate that omega-3 FA supplementation will be useful in minimizing the inflammatory cascade and therefore improving cardiac function in individuals with OSA.…”
mentioning
confidence: 84%
“…Due to the condensed production of Leukotriene B4 and Thromboxane A2, may play a role as an antiinflammatory effect are raised up in the inflamed intestinal mucosa of patients thru crohn's disease or inhibition of the synthesis of cytokines such as interleukin-1 beta and tumour necrosis factor 37 and hence can also scavenge free radicals.…”
Section: Anti-inflammatory Effectmentioning
confidence: 99%
“…The person may experience nervous or neural system problems which includes 37 Multiple Sclerosis (chronic inflammatory disease which leads to plaques and tissue injuries in central nervous system). Hence, indicating that may be exposure of genotoxic pollutants through various mercury mechanisms is responsible for the DNA damage due to single or double strand breakages, leading to variants of adverse health effects entering to food chain and ultimately hampering human health and life 46 .…”
Section: Harmful Effectsmentioning
confidence: 99%